Thyrotropin-Releasing Hormone-Containing Axons Innervate Histaminergic Neurons in the Tuberomammillary Nucleus - Sárvári, Anna (2012)
Recent studies indicate that the effect of thyrotropin-releasing hormone (TRH) on the regulation of food intake may be mediated by histaminergic neurons. To elucidate the anatomical basis for a functional relationship between TRH- and histamine-synthesizing neuronal systems, double-labeling immunocytochemistry was performed on the tuberomammillary nucleus (TMN) of rats, the exclusive location of histaminergic neurons. TRH-immunoreactive (IR) innervation of the histaminergic neurons were detected in all five subnuclei (E1-5) of the TMN, but was most prominent in the E4 and E5 subnuclei where 100% of the histamine-IR neurons were contacted. The number of TRH-IR varicosities in contact with histamine-IR neurons was also greatest in the E4 and E5 subnuclei, averaging 27.0±1.2 in E4 and 7.9±0.5 in E5. Somewhat fewer histamine-IR neurons were juxtaposed by TRH-IR varicosities in E2 and E3 and contacted by 6.3 ± 0.2 and 6.8 ± 0.2 varicosities/innervated cell, respectively. The number of juxtapositions of TRH-IR axon varicosities with histamine-IR neurons was the lowest in the E1 subnucleus (85.7±0.9%; 4.0±0.2 varicosities/innervated cell). Ultrastructural analysis demonstrated that TRH-IR axons established both asymmetric and symmetric type synapses on the perikaryon and dendrites of the histamine-IR neurons, although the majority of synapses were asymmetric type. These data demonstrate that TRH neurons heavily innervate histaminergic neurons in all subdivisions of the TMN, with the densest innervation in the E4 and E5 subdivisions, and are likely to exert activating effects.